UTILISATION OF Moringa oleifera LAM. SEED AS PROTEIN SOURCE IN THE DIETS OF BROILER CHICKENS (2017)
Conventional vegetable protein ingredients in poultry feed are costly and relatively scarce. Moringa oleifera Seed Meal (MSM) is an oil seed rich in protein, which can be exploited as an alternative vegetable protein source. However, the potential of MSM as a protein source for broiler production has not been adequately documented. Therefore, this study was conducted to investigate the utilisation of MSM as a protein source in the diets of broiler chickens. Moringa seeds were harvested and apportioned into four parts representing T1, T2, T3 and T4. The T1 was raw, while T2, T3 and T4 were soaked in water (200 g/L) for 1, 2, and 3 hours, respectively. The seeds were then sun-dried, milled and analysed for Crude Protein (CP, %), alkaloid (%), saponin (%) and tannin (%), using standard procedures. The protein quality of MSM was assessed using forty weanling albino rats (42.35±0.83 g) randomly allotted to four diets containing 10.0% casein (D1), 10.0% raw MSM (D2), 10.0% 3-hour Water-soaked MSM (WMSM, D3) and a protein free diet (D4) fed for 21 days. Protein quality: Biological Value (BV, g), Protein Efficiency Ratio (PER) and Net Protein Utilisation (NPU, g) were determined using standard procedures. Two hundred and fifty 1-day old broiler chicks were randomly allotted to five diets wherein Full-fat Soyabean (FS) was replaced with 3-hour WMSM at 0.0, 25.0, 50.0, 75.0 and 100.0%. Daily Weight Gain (DWG, g/bird), Feed Intake (FI, g/bird), and Feed Conversion Ratio (FCR) were measured. Blood (5mL) samples were collected for determination of Packed Cell Volume (PCV, %), Red Blood Cell (RBC x106/µL) and White Blood Cell (WBCx103/µL) counts, Total Cholesterol (TC, mg/dL), triglycerides (mg/dL) and immunoglobulins: IgG, IgA and IgM (IU/dL) using standard procedures. Data were analysed using descriptive statistics and ANOVA at α0.05. The CP of T1 (35.4±0.7), T2 (35.3±0.4), T3 (35.7±0.8) and T4 (36.1±0.7%) were similar, while alkaloid, saponin and tannin content ranged from 0.05±0.10 (T4) to 0.07±0.04 (T1), 0.42±0.50 (T4) to 1.17±0.28 (T1) and 0.05±0.02 (T4) to 0.06±0.02 (T1), respectively. The BV ranged from 54.87±5.54 (D4) to 65.69±5.70 (D1), PER from 0.63±0.08 (D4) to 1.10±0.33 (D1) and NPU from 15.86±1.22 (D4) to 44.37±4.31 (D1). The birds fed 100.0%WMSM had least DWG (0.63±0.11), while birds on 100.0%FS had the highest (1.30±0.15). The FI was least in 100.0%WMSM (2.19±0.86) and highest in 100.0%FS (30.00±7.86). The FCR ranged from 2.45±0.32 (100.0%FS) to 3.48±0.26 (100.0%WMSM). The PCV ranged from 29.7±0.54 (100.0%FS) to 34.5±0.86 (100.0%WMSM), RBC from 2.98±0.06 (75.0%WMSM) to 3.44±0.08 (25.0%WMSM) and WBC from 1.25±0.52 (100.0%FS) to 1.53±0.64 (100.0%WMSM). Birds fed 100.0%WMSM had least TC (157.67±10.72) compared with 100.0%FS (206.33±13.52) and triglycerides, which ranged from 56.00±3.26 (100.0%WMSM) to 85.36±5.35 (100.0%FS). The IgG, IgA and IgM recorded for birds on WMSM diets ranged from 0.62±0.36 (100.0%FS) to 0.73±0.40 (100.0%WMSM), 0.31±0.18 (100.0%FS) to 0.49±0.15 (100.0%WMSM) and 0.09±0.04 (100.0%FS) to 0.15±0.08 (100.0%WMSM), respectively. Three hours water-soaked Moringa oleifera seed meal at 100.0% inclusion reduced growth, enhanced immunoglobulins profile and lowered total cholesterol of broiler chickens.